Dexamethasone Predisposes Human Erythroblasts Toward Impaired Lipid Metabolism and Renders Their ex vivo Expansion Highly Dependent on Plasma Lipoproteins - Zingariello, Maria; Bardelli, Claudio; Sancillo, Laura; Ciaffoni, Fiorella; Genova, Maria Luisa; Girelli, Gabriella; Migliaccio, Anna Rita (Frontiers in Physiology, 2019)
Cultures of stem cells from discarded sources supplemented with dexamethasone, a synthetic glucocorticoid receptor agonist, generate cultured red blood cells (cRBCs) in numbers sufficient for transfusion. According to the literature, however, erythroblasts generated with dexamethasone exhibit low enucleation rates giving rise to cRBCs that survive poorly in vivo. The knowledge that the glucocorticoid receptor regulates lipid metabolism and that lipid composition dictates the fragility of the plasma membrane suggests that insufficient lipid bioavailability restrains generation of cRBCs. To test this hypothesis, we first compared the expression profiling of erythroblasts generated with or without dexamethasone. This analysis revealed differences in expression of 55 genes, 6 of which encoding proteins involved in lipid metabolism. These were represented by genes encoding the mitochondrial proteins 3- Hydroxymethyl-3-Methylglutanyl-CoA lyase, upregulated, and 3-Oxoacid CoA-Transferase1 and glycerol-3-phosphate acyltransferase1, both downregulated, and the proteins ATP-binding cassette transporter1 and Hydroxysteroid-17-Beta-Dehydrogenase7, upregulated, and cAMP-dependent protein kinase catalytic subunit beta, downregulated. This profiling predicts that dexamethasone, possibly by interfering with mitochondrial functions, impairs the intrinsic lipid metabolism making the synthesis of the plasma membrane of erythroid cells depend on lipid-uptake from external sources. Optical and electron microscopy analyses confirmed that the mitochondria of erythroblasts generated with dexamethasone are abnormal and that their plasma membranes present pebbles associated with membrane ruptures releasing exosomes and micro-vesicles. These results indicate that the lipid supplements of media currently available are not adequate for cRBCs. To identify better lipid supplements, we determined the number of erythroblasts generated in synthetic media supplemented with either currently used liposomes or with lipoproteins purified from human plasma [the total lipoprotein fraction (TL) or its high (HDL), low (LDL) and very low (VLDL) density lipoprotein components]. Both LDL and VLDL generated numbers of erythroid cells 3-2-fold greater than that observed in controls. These greater numbers were associated with 2-3-fold greater amplification of erythroid cells due both to increased proliferation and to resistance to stress-induced death. In conclusion, dexamethasone impairs lipid metabolism making ex-vivo expansion of erythroid cells highly dependent on lipid absorbed from external sources and the use of LDL and VLDL as lipid supplements improves the generation of cRBCs.